Development of Learning Media based on Kinovea Application in Biomechanics Course - Prabowo, Andika; Pujianto, Dian; Raibowo, Septian; Defliyanto; Yarmani (UNIB Press, 2023)
This study aims to facilitate Physical Education Study Program students with the renewal of learning media based on the kinovea application, especially in biomechanics courses which not only learn theoretically but have elements of measurement and analysis of motion in humans, this study uses research and development methods using bolt and galt designs. 8 stages. The subjects of this study were physical education students in semester 5, the results showed that the level of validation of learning media from material experts and media experts was 4.13 eligible categories and 3.3 eligible categories. The results of the small scale trial show an average value of 4.1 with the Eligible category. The results of large scale trials show an average value of 3.45 in the appropriate category. Based on the results at the validation stage and small-scale and large-scale trials, this study resulted in a kinovea application-based learning media in the biomechanics course of the Bengkulu University physical education study program.